Analysis of the proteome of intracellular Shigella flexneri reveals pathways important for intracellular growth - Pieper, Rembert; Fisher, C R; Suh, Moo-Jin; Huang, S-T; Parmar, P; Payne, S M (Infection and immunity, 2013)
Global proteomic analysis was performed with Shigella flexneri strain 2457T in association with three distinct growth environments: S. flexneri growing in broth (in vitro), S. flexneri growing within epithelial cell cytoplasm (intracellular), and S. flexneri that were cultured with, but did not invade, Henle cells (extracellular). Compared to in vitro and extracellular bacteria, intracellular bacteria had increased levels of proteins required for invasion and cell-to-cell spread, including Ipa, Mxi, and Ics proteins. Changes in metabolic pathways in response to the intracellular environment also were evident. There was an increase in glycogen biosynthesis enzymes, altered expression of sugar transporters, and a reduced amount of the carbon storage regulator CsrA. Mixed acid fermentation enzymes were highly expressed intracellularly, while tricarboxylic acid (TCA) cycle oxidoreductive enzymes and most electron transport chain proteins, except CydAB, were markedly decreased. This suggested that fermentation and the CydAB system primarily sustain energy generation intracellularly. Elevated levels of PntAB, which is responsible for NADPH regeneration, suggested a shortage of reducing factors for ATP synthesis. These metabolic changes likely reflect changes in available carbon sources, oxygen levels, and iron availability. Intracellular bacteria showed strong evidence of iron starvation. Iron acquisition systems (Iut, Sit, FhuA, and Feo) and the iron starvation, stress-associated Fe-S cluster assembly (Suf) protein were markedly increased in abundance. Mutational analysis confirmed that the mixed-acid fermentation pathway was required for wild-type intracellular growth and spread of S. flexneri. Thus, iron stress and changes in carbon metabolism may be key factors in the S. flexneri transition from the extra- to the intracellular milieu.